Zone identification based on features with high semantic richness and combining results of separate classifiers. Issue 4 (2nd October 2018) - Badie, Kambiz; Asadi, Nasrin; Tayefeh Mahmoudi, Maryam
ABSTRACT: In this paper, we propose a new approach to zone identification which is based on considering features with high semantic richness. Out of the scenarios of selecting features for identifying a zone based on classifying the sentences in a text, we came to notice that in the scenario where specialized names belonging to a text's domain and mode of the verbs together with reduced versions of conventional features, including history, are taken into account, an accuracy rate of 61% (resp. 81%) is obtained which is higher than that belonging to Liakata's (resp. Fisas's) approach. Also, to have a genuine comparison, both Liakata's and Fisas's corpora are used in our experiments. Such accuracy is obtained at the place where less computational cost for extracting the features was decreased. In order to improve the accuracy of zone identification, a decision-level fusion process based on combining the results of separate classifiers, was considered. With regard to this, two fusion techniques of 'majority voting' and 'average of probabilities' were used. Experimentations show the fact that ensemble of 'Logistic Regression', 'Support Vector Machine' and 'Neural Network' as classifiers yields the best performance. Also 'majority voting' was shown to perform a bit better than 'average of probabilities'.